Monastic Bodies : Discipline and Salvation in Shenoute of Atripe - Schroeder, Caroline T., 1971- (Book collections on Project MUSE., 2007)
An in-depth examination of the asceticism practiced at the White Monastery in Upper Egypt in the fifth century, using diverse sources, including monastic rules, theological treatises, sermons, letters, and material culture.